Influence of comprehension in english language, age, home and school environments on students' achievement in secondary school economics in Ibadan (2008)
The study sought to explain the influence of comprehension in english language,age, home and school enviroments on students' achievemeny in secondary school economics in Ibadan. It was an ex-post facto research, and data were collected in order to answer six research questions. The sample comprised of 1,300 senior secondary II economics students (730 males and 570 females), drawn from 26 schools using stratified random sampling technique. It used four valid and relaible instruments to collect data on the relevant variables. Data collected were subjected to frequency, t-test, and multiple regression analyses. The result shows that the level of comprehension in english language was generally low in all the schools, with only 22.6% obtaining credit or distinction between variables, comprehension in english language and age predicted achievement in economics, and that comprehension in english language is the most potent contributor to the prediction. Also, age is the next prediction to comprehension in english language, but its influence is negative; this is to say that the higher the age, the lesser the achievement in economics, and vice versa. Though the home and the school enviroments' prediction on achievement in economics is not significant, it is however positively related to economics achievement. These findings have implications for policies and strategies on the teaching, learning and evaluation of economics in secondary schools in Ibadan municipality.